2022
DOI: 10.1038/s41598-022-11115-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of land use in the catchment area of small waterbodies on the quality of water and plant species composition

Abstract: Land use significantly affects the function of waterbodies in landscape. Although there have been numerous studies on the influence of the catchment area on the trophic and ecological status of waterbodies, still is not reached an agreement on the width of the buffer zone that is necessary for effective protection of waterbodies. The aim of the study was to show whether small waterbodies are predominantly influenced by land use in the entire catchment area or only in the zone extending 100 or 200 m away from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…These findings are also consistent with those of Szpakowska et al (2022), where a canonical correspondence analysis showed that farming, had the greatest influence on water quality and vegetation in small waterbodies. The analysis specifically showed that arable land located in the buffer zone, extending to 100m form the shoreline had the greatest influence.…”
Section: Crop and Pasturesupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are also consistent with those of Szpakowska et al (2022), where a canonical correspondence analysis showed that farming, had the greatest influence on water quality and vegetation in small waterbodies. The analysis specifically showed that arable land located in the buffer zone, extending to 100m form the shoreline had the greatest influence.…”
Section: Crop and Pasturesupporting
confidence: 89%
“…It was also determined that catchment area is a good predictor of both permits and permits per kilometre shoreline. In a study by Szpakowska et al (2022), the authors concluded that the catchment areas of waterbodies significantly affect small aquatic ecosystems.…”
Section: Catchment Area and Catchment To Lake Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1970s, remote sensing, GIS, and statistical techniques have been used to assess the interactions between terrestrial and aquatic systems (Xu et al, 2001). Numerous studies have investigated the relationship between landscape composition and surface water quality ( (Wang et al, 2023), cellular automata-Markov models (Yao et al, 2023), arti cial neural networks (Wang & Zhang, 2018;Zhou et al, 2016), redundancy analysis (Zhao et al, 2015), canonical correspondence analysis (CCA) and canonical regression analysis (Szpakowska et al, 2022;Luo et al, 2020;Luo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…About three-quarters of the Earth's land surface have been altered within the last millennium as a result of human activities and natural processes [1][2][3], which also brings a variety of ecological and environmental problems [4][5][6]. Changes in land use and land cover affect directly the Earth's energy balance and the biogeochemical cycle, and also have an impact on hydrological processes and water cycles [7], climate change (precipitation and temperature) [8], carbon cycles [9], biodiversity [10], and forest degradation [11]. For example, at the expense of ecological functions, large expanses of lowland tropical rainforest have been converted to large-scale commercial plantations or small-scale mosaic agricultural landscapes in Indonesia [12].…”
Section: Introductionmentioning
confidence: 99%